2011
DOI: 10.1039/c0dt00822b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of a guanine derivative coordinated to a Pt(iv) complex initiated by intermolecular nucleophilic attacks

Abstract: In this study we report that fac-[Pt(IV)(dach)(9-EtG)Cl(3)](+) (dach = d,l-1,2-diaminocyclohexane, 9-EtG = 9-ethylguanine) in high pH (pH 12) or phosphate solution (pH 7.4) produces 8-oxo-9-EtG and Pt(II) species. The reaction in H(2)(18)O revealed that the oxygen atom in hydroxide or phosphate ends up at the C8 position of 8-oxo-G. The kinetics of the redox reaction was first order with respect to both Pt(IV)-G and free nucleophiles (OH(-) and phosphate). The oxidation of G initiated by hydroxide was approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(4 reference statements)
0
7
1
2
Order By: Relevance
“…by phosphate. 385,386 The platinum(IV) complex cis,cis,trans -[Pt(NH 3 ) 2 Cl 2 (OH) 2 ] was reported to cleave double-stranded DNA but this reactivity was subsequently shown to arise from molecules of H 2 O 2 that co-crystallized with the platinum(IV) complex. 387,388 …”
Section: Platinum(iv) Complexes With Non-cisplatin-like Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…by phosphate. 385,386 The platinum(IV) complex cis,cis,trans -[Pt(NH 3 ) 2 Cl 2 (OH) 2 ] was reported to cleave double-stranded DNA but this reactivity was subsequently shown to arise from molecules of H 2 O 2 that co-crystallized with the platinum(IV) complex. 387,388 …”
Section: Platinum(iv) Complexes With Non-cisplatin-like Mechanismsmentioning
confidence: 99%
“…The oxidation of guanine was confirmed as was the ability of the oxidation to occur with guanine bases in double-stranded oligonucleotides. The reactions typically occurred on the order of days, and theoretical calculations suggest that the reaction proceeds via a cyclic 5′,8-phosphodiester intermediate. , Analysis of kinetic data revealed that platinum­(II) centers can catalyze the reaction, which is initiated by intermolecular nucleophilic attack, for example, by phosphate. , Another form of platinum­(IV)-mediated DNA damage was reported following the observation that cis , cis , trans -[Pt­(NH 3 ) 2 Cl 2 (OH) 2 ] could cleave double-stranded DNA, but this reactivity was subsequently shown to arise from molecules of H 2 O 2 that cocrystallized with the platinum­(IV) complex. , …”
Section: Platinum(iv) Complexes With Noncisplatin-like Mechanisms Of ...mentioning
confidence: 99%
“…The rate for [1] + ViFc k 2 = 2.80 AE 0.1 M À1 s À1 at 22 1C was 160 times faster than the control reaction TzPy + ViFc k 2 = 0.0180 M À1 s À1 at 22 1C. The Eyring analysis 19 of [1] + ViFc found DH ‡ = 22.6 kJ mol À1 and DS ‡ = À150 J mol À1 K À1 , with DG ‡ (25 1C) = 68 kJ mol À1 . The Eyring analysis of TzPy + ViFc showed a small increase in the DH ‡ = 27 kJ mol À1 , however the DS ‡ = À192 J mol À1 K À1 contributed more to the DG ‡ (25 1C) = 84 kJ mol À1 .…”
mentioning
confidence: 92%
“…35,37,38 O mais reativo dentre os complexos estudados, a tetraplatina 3 ([PtCl 4 (dach)]), oxida várias bases do DNA deri adas da gua i a, por e e plo, 5'-dGMP, 39 3'dGMP, 40 9-etilguanina 41 (Esquema 6), assim como sequências de bases. Este processo ocorre em duas etapas: i) substituição de um ligante cloreto pela base do DNA, que se coordena à Pt 4+ através do N7 e torna o C8 deficiente em densidade eletrônica e ii) transferência eletrônica, iniciada pelo ataque nucleofílico ao C8 da base coordenada, por nucleófilos externos 41 ou intramoleculares 37 (OHou PO 4…”
Section: Esquema 5 Produtos Da Redução Do Complexo Ciscistrans-[ptclunclassified
“…Esquema 6. Mecanismo proposto para as reações da tetraplatina 3 com derivados da guanina (G) [39][40][41] Foi demonstrado que a substituição do ligante cloreto pelas bases 5'-e 3'-dGMP (G) nos complexos de Pt 4+ [PtCl 4 (en)] (en = etilenodiamina) e [PtCl 4 (dach)] 3 37 é catalisada por complexos de Pt 2+ , através do mecanismo clássico de Basolo e Pearson. 36,42 Como ilustrado no Esquema 7, a substituição pode ser vista, formalmente, como resultando da adição oxidativa, ao catalisador, de um ligante cloro do complexo de Pt 4+ e de uma G.…”
Section: Esquema 5 Produtos Da Redução Do Complexo Ciscistrans-[ptclunclassified